Overtraining following intensified training with normal muscle glycogen - Snyder, A. C.; Kuipers, H.; Cheng, B.; Servais, R.; Fransen, E. (Medicine & Science in Sports & Exercise, 1995)
This study assessed whether the consumption of adequate amounts of CHO to maintain glycogen levels would protect athletes (trained cyclists; N = 8) from entering an overtained state. Since no single physiological symptom or set of symptoms has been found to be associated with overtraining (p. 1065), five of the most observed symptoms were measured. If a subject displayed three of these five, it was inferred that an overtrained state had been achieved. The five symptoms were: a) decreased maximal workload, b) reduced HRmax, c) reduced resting plasma cortisol levels, d) reduced HLamax to RPE ratio, and e) an increased number of affirmative responses to a daily questionnaire about exercise stress symptoms. Implication: Overtrained states occurred despite maintaining consistent levels of muscle glycogen. Other factors, varying according to the individual, were associated with overtraining. Psychological reports of well-being were the most consistent indicators of overtraining.